Factors associated with the emergence of integrase resistance mutations in patients failing dual or triple integrase inhibitor-based regimens in a French national survey. (7th July 2021) - Marcelin, Anne-Genevieve; Charpentier, Charlotte; Bellecave, Pantxika; Abdi, Basma; Chaix, Marie-Laure; Ferre, Virginie; Raymond, Stephanie; Fofana, Djeneba; Bocket, Laurence; Mirand, Audrey; Le Guillou-Guillemette, Helene; Montes, Brigitte; et al.
Abstract: Background: Successful 2-drug regimens (2DRs) for HIV were made possible by the availability of drugs combining potency and tolerability with a high genetic barrier to resistance. How these deal with resistance development/re-emergence, compared with 3DRs, is thus of paramount importance. Materials and methods: A national survey including patients who were either naive or experienced with any 2DR or 3DR but failing integrase strand transfer inhibitor (INSTI)-containing regimens [two consecutive plasma viral load (VL) values >50 copies/mL] was conducted between 2014 and 2019. Genotypic resistance tests were interpreted with the v28 ANRS algorithm. Results: Overall, 1104 patients failing any INSTI-containing regimen (2DRs, n = 207; 3DRs, n = 897) were analysed. Five hundred and seventy-seven (52.3%) patients were infected with a B subtype and 527 (47.3%) with non-B subtypes. Overall, 644 (58%) patients showed no known integrase resistance mutations at failure. In multivariate analysis, factors associated with the emergence of at least one integrase mutation were: high VL at failure (OR = 1.24 per 1 log10 copies/mL increase); non-B versus B subtype (OR = 1.75); low genotypic sensitivity score (GSS) (OR = 0.10 for GSS = 2 versus GSS = 0–0.5); and dolutegravir versus raltegravir (OR = 0.46). Although 3DRs versus 2DRs reached statistical significance in univariate analysis (OR = 0.59, P = 0.007), the variable is not retained in the final model. Conclusions: This study is one of the largest studies characterizing integrase resistance in patients failing any INSTI-containing 2DR or 3DR in routine clinical care and reveals factors associated with emergence of integrase resistance that should be taken into consideration in clinical management. No difference was evidenced between patients receiving a 2DR or a 3DR.